2013
DOI: 10.1039/c3tb00503h
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-crosslinked alginate gel for patient-controlled drug delivery systems: regulation of host–guest interactions with mechanical stimuli

Abstract: Macroscopic mechanical force has attracted much attention as an existing yet novel energy source for modification of molecular interactions and molecular reactivity. Although various molecular level phenomena have been controlled by using macroscopic mechanical forces, control of host-guest inclusion has not been a research target. Here we report a novel controlled release system triggered by a mechanical stimulus. Release of ondansetron (ODN), an anti-emetic drug, from a designer hydrogel composed of a b-cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 29 publications
0
110
0
2
Order By: Relevance
“…Bibby et al 66 reported a crosslinking between CD and polymeric formulations which resulted in a decrease in the polymer mesh size, thus decreasing drug release. Izawa et al 67 designed a unique system for controlled release of ondansetron which was composed of β-CD crosslinked with alginate as the main chain polymer. Many authors reported the advantages of using β-CD and chitosan together in controlling drug release from polymeric matrices.…”
Section: Evaluation Of Agnps-loaded Hydrogelsmentioning
confidence: 99%
“…Bibby et al 66 reported a crosslinking between CD and polymeric formulations which resulted in a decrease in the polymer mesh size, thus decreasing drug release. Izawa et al 67 designed a unique system for controlled release of ondansetron which was composed of β-CD crosslinked with alginate as the main chain polymer. Many authors reported the advantages of using β-CD and chitosan together in controlling drug release from polymeric matrices.…”
Section: Evaluation Of Agnps-loaded Hydrogelsmentioning
confidence: 99%
“…The molecular machine can catch and release guest molecules based on hand-motion-like microscopic motions. Similarly, control of molecular phenomena including chiral recognition [48,49], nucleic acid base discrimination [50], glucose detection by indicator displacement assay [51], and controllable drug delivery [52] by macroscopic mechanical motions have been demonstrated using interfacial media and related structures. These are realistic examples of accessing molecular-level functions from the macroscopic world.…”
Section: Future Approaches For Access From Macro To Moleculementioning
confidence: 98%
“…The thermodynamic benefits originate from the lower Gibbs free energy for those complexes [32]. In addition, various applications related to the increased aqueous solubility [33], controlled delivery [34], sensing [35], and separation tools could be reported on the basis of host-guest chemistry [36]. In this review, an overview of history, biosynthesis, purification, structure, classification, properties, and current applications of cyclic b-glucans and their derivatives as a new family of carbohydrate hosts will be presented.…”
Section: Introductionmentioning
confidence: 99%